EXPERIENCES: LEARNING AND OBSERVING WHILE LIVING - Müller, César Augusto; Oliveira, Clara Costa (Cadernos de Educação Tecnologia e Sociedade, 2016)
The present research fits the paradigm of complexity, which opposes to the one that preceded it — the mechanicist, and that still prevails in many of the researches carried out in several areas of knowledge, among them, those of formal and non-formal education. Many theories compose the paradigm of Complexity, one of them, the biological theory of Autopoiesis by Maturana and Varela shows us the singularity of each living creature through its closed organization (yet not isolated) that occurs simultaneously in structural interaction with other living beings. That theory was essential for this study, which is linked to non-formal and informal dimension of education. The main intention was to observe and understand the act of causing emotion in the process of selfconstitution and complexification of the subjects involved through experiences as event using the Digital Information and Communication Technology. It was on this conceptual basis that this intervention-research was constituted. Through it gradually researcher and researched subjects formed a complex unit, working on themselves and with others, disturbing and rebuilding themselves as unique and irreplaceable people and simultaneously as a community with a project of common life that became essential in the (re) assignment of meaning to (in) the world.